Critical Thinking Development in Culturally Responsive Teaching at the Primary School Level: A Systematic Literature Review - Ikhsan, Muhammad; Agustini, Rudiana; Erman; Salim, Nuragus (Technium Social Sciences Journal, 2026)
Increasing classroom diversity and the rapid digitization of elementary education have intensified the need to embed critical thinking (CT) within culturally responsive teaching (CRT). However, empirical synthesis on this intersection remains limited, particularly in Global South contexts and technology- enhanced learning (TEL) environments. This multi-source systematic literature review (SLR) synthesizes evidence from 33 studies across three complementary corpora: (A) Scopus-indexed studies examining CT-CRT integration in primary schools (2016–2025); (B) Scopus and Web of Science studies on culturally responsive pedagogy in TEL environments in developing-country contexts (2020–2025); and (C) supplementary Indonesian practitioner evidence retrieved via Google Scholar (2020–2025) to address indexation gaps. Following PRISMA 2020 guidance [12] and thematic synthesis procedures [13], seven higher-order themes were identified: cultural integration as a CT scaffold; teacher epistemic humility as a constitutive variable; equity and structural determinants; cross-cultural variability in CT constructs; ethnoscience and indigenous knowledge in digital STEM; systemic barriers to CRP-EdTech adoption; and HOTS-CRT curriculum development. Quantitative evidence indicates that culturally aligned instruction can yield statistically significant CT gains, while qualitative evidence suggests that superficial cultural inclusion without epistemic transformation may undermine learning. The review advances three theoretical propositions: teacher epistemic humility is constitutive to authentic CRT; CT sub-competency structures are culturally modulated; and HOTS- CRT integration is a curriculum-development priority in developing-country elementary education.